Getting In : How Not to Apply to Medical School. - Jung, Dr. Paul (Medical Student Survival Series., 1999)
Getting In: How Not To Apply to Medical School is a tough, practical guide for people storming the ramparts of medical school admission boards. Paul Jung takes the pre-med or second-career aspirant from pre-application experiences through the application process with a very practical approach. The book is filled with the pitfalls and misconceptions applicants frequently make, rendering the subtitle particularly apt and (for those terrified of the unknowns) eminently appealing. The volume also includes self-diagnostic sections and common pitfalls to avoid when applying to medical school. C.